Differences in REG1B-associated biomarkers in patients with and without chronic pancreatitis - Guevara-Tirado, Alberto (2025)
Introduction: REG1B is a protein involved in cell regeneration, whose regulation may vary depending on the health or disease status. Objective: to identify pancreatic biomarkers associated with REG1B in patients with chronic pancreatitis and healthy subjects. Materials and method: Secondary data cut-off study of 302 patients. The variables were: regenerating protein of the islets of Langerhans 1B and 1A (REG1B; REG1A), hyaluronan receptor 1 of the lymphatic endothelium (LYVE-1), Trefoil factor-1 (TFF1), carbohydrate antigen 19-9 (CA19-9). Spearman correlation, multiple linear regression and scatter plot were used. Results: In healthy subjects (n=183), REG1B showed significant and positive correlations with LYVE1 (rho=0.459,p<0.001), TFF1 (rho=0.549,p<0.001) and REG1A (rho=0.780,p<0.001). There was no significant correlation with CA19-9 (rho=0.153,p=0.144). In chronic pancreatitis (n=119), positive correlations between REG1B and LYVE1 (rho=0.464,p<0.001), TFF1 (rho=0.645,p<0.001) and REG1A (rho=0.770,p<0.001) persisted, but the correlation with CA19-9 became significant (rho=0.268,p=0.033). The linear regression analysis model in healthy subjects was highly significant (F=36.635, p<0.001), explaining 86.90% of the variability in REG1B, with TFF1 (B=0.136, t=7.057, p<0.001) and LYVE1 (B=8.253, t=3.737, p=0.001) as the main predictors. In patients with chronic pancreatitis, the model was less robust (F=3.523, p=0.016), explaining 26.50% of the variability, with LYVE1 being the only significant predictor (B=15.956, t=3.060, p=0.004). Conclusions: The dynamics of the biomarkers CA19-9, TFF1, LYVE1, REG1A with REG1B are significantly altered in chronic pancreatitis. These findings highlight biological differences in REG1B regulation between disease and health states.